Chapter 6 Idrætspsykologi med et community psykologisk afsæt - Ryom, Knud (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The overall purpose of this study was to examine how a transformative and community psychological approach could affect a socially challenged neighbourhood and participants´ perceptions of involvement (young boys, 12-16 years). A social research experiment lasting 2 years was co-created between researchers, practitioners and participants. A multi-method approach was used to ensure that thorough and socially robust knowledge was produced. Methods used included questionnaires, interviews, fieldwork and observations. Although several notable results emerged throughout the intervention period, the most important results were related to the significance of the overall approach regarding these results. Despite the challenges faced by researchers, when engaging youth at the margins of society in a co-creation process, the approach seemed valuable. Giving the participants the possibility to engage themselves, through empowerment initiatives, seems to be a confounding reason for the success of the project. Hence, this article will focus upon the benefits of using a community psychological approach when working with exercise psychology in a socially deprived community."